Physical and match characteristics of English elite academy soccer players: differences between age groups - Dickinson, B.; Jones, P.; Comfort, P. (The Journal of Strength and Conditioning Research, 2025)
The purpose of this study was to evaluate physical and match characteristics of elite academy soccer players and determine differences between age groups. Sixty elite academy soccer players, including u15 (Subject: N = 15; age: 14.64 ± 0.25 years; mass: 59.88 ± 9.12 kg; height: 171.0 ± 6.7 cm), u16 (Subject: N = 15; age: 15.42 ± 0.36 years; mass: 65.11 ± 8.70 kg; height: 175.0 ± 7.2 cm), u18 (Subject: N = 15; age: 17.00 ± 1.00 years; mass: 72.85 ± 7.43 kg; height: 179.0 ± 6.4 cm), and u23 (Subject: N = 15; age: 19.60 ± 0.85 years; mass: 77.47 ± 7.03 kg; height: 181.0 ± 7.7 cm) participated in the study. Significant differences were seen in anthropometrics and maturation (p = 0.031), absolute eccentric hamstring strength (p = 0.033), absolute isometric mid-thigh pull performances ([IMTPs] p = 0.026), jump height and reactive strength index from the 10-5 reactive jump tests (p = 0.015), most countermovement jump variables (p = 0.040), and the 30-15IFT (p = 0.012), with better performances in older age groups. Absolute and relative (i.e., divided by time) match characteristics were significantly greater (p = 0.038) in older age groups compared with younger age groups. Results indicate that older, more mature players demonstrate better performance in eccentric hamstring strength and IMTP peak force, based on absolute measures; however, the differences were negated when ratio scaled (i.e., divided by body mass). Strength training practices need to be improved to ensure that strength increases exceed those expected with increases in mass associated with maturation.